Religion and healing among Somalis in Sweden when experiencing illness and suffering - Wedel, Johan (2014)
Today, about 40 000 Somalis live in Sweden. This paper, based on anthropological fieldwork in the city of Gothenburg, inquires into the role of religion among Somali-Swedes when experiencing illness and suffering. When ill, many Somalis turn to both biomedicine (“Western medicine”) and Islam. Faith in Islam and its Holy book, the Qur’an, gives not only religious guidance but also a profound meaning to ill-health in a way that biomedicine cannot. The paper shows how the biomedical view of illness, with its individualized perspective and mind-body distinction, is challenged by a religious and more holistic view of illness and suffering. By presenting a number of cases, it is shown how illness is sometimes manifested as spirit (jinn) possession, the evil eye, sorcery and curses, and related to existential issues and to the social world of the sufferer. To deal with these afflictions, people may use Qur’an recitations and other techniques involving the Qur’an, herbal oils, rituals of exorcism, and they may travel to powerful healers (sheikhs) in Somalia or neighbouring countries.